Advanced UV Spectrophotometric Method Development and Validation for Simultaneous Estimation of Azelnidipine and Telmisartan in Pharmaceutical Dosage Form - Suthar, Pallavi; Mashru, Rajashree (Indian Journal of Pharmacy & Drug Studies, 2023)
The presented research work aims to develop and validate three advanced UV spectrophotometric methods for the simultaneous estimation of Azelnidipine (AZL) and Telmisartan (TEL). These methods offer a higher degree of sensitivity than already-existing methods of analysis. By implementing advanced spectroscopic techniques such as the simultaneous method, Q-ratio method, and first derivative spectroscopy method. These methods offer a higher degree of sensitivity than already-existing methods of analysis. by implementing advanced spectroscopic techniques such as the simultaneous method, Q-ratio method, and first derivative spectroscopy method. The linearity of the three methods was in the range of 2 μg/ml to 12 μg/ml for AZL and 10 μg/ml to 50 μg/ml for TEL. The correlation coefficients for simultaneous estimation were 0.999 and 0.998 for AZL and TEL, respectively, and 0.9992 and 0.9989 for AZL and TEL, respectively, for the first derivative method, whereas the correlation coefficients for the Q-ratio method were 0.999 and 0.9988, respectively. The LOD values obtained by the simultaneous estimation method were found to be lower as compared to those obtained by the first derivative method and the Q-ratio method, proving that the sensitivity of the simultaneous estimation method is high.